Horizontal Compression Test: A Proposed Method for Indirect Determination of Tensile Strength of Stiff Soils and Soft Rocks - Guan, Fanfan; Li, Yanrong; Gao, Guohong; Zachert, Hauke; Eichhoff, Gerald; Beroya-Eitner, Mary Antonette (Frontiers in Earth Science, 2022)
Tensile strength is an important parameter in many engineering activities and problems. For instance, tension cracks in loess influence the stability of loess slopes and to a great extent determine the ultimate slope failure, especially in the modes of crack–sliding and toppling. Therefore, accurate measurement of tensile strength of geomaterial is a necessity for implementation of geotechnical or geological engineering, such as slope and tunnel stabilization. Commonly used methods for tensile strength measurement have important limitations and shortcomings, which become increasingly serious when dealing with soil and soft rocks. This study developed a new indirect tensile test, the horizontal compression test, for use with these materials. This method is not only simple, in terms of sample preparation and test operation, but also addresses the eccentric force and stress concentration problems, which are common in conventional tensile tests. To evaluate the method’s validity, a laboratory test campaign was performed to compare its performance with the closely related Brazilian test and the ISRM-suggested direct tensile test. Results show that the tensile strength values obtained with the proposed method are more stable than those obtained with either the Brazilian test or the ISRM-suggested tensile test. Moreover, the tensile strengths obtained with the proposed method and the ISRM-suggested tensile test are strongly correlated. Thus, the proposed method can and may even be more suitable to determine the tensile strength of soil and soft rocks.